PERSEPSI KHALAYAK TERHADAP PROGRAM TAKE AND GIVE RADIO SUARA KENDARI (STUDI PADA MAHASISWA ILMU KOMUNIKASI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK - Andi Firman Setiawan (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2017)
ABSTRACTThe purpose of this study is to determine the Perception of Public toward Take and Give Program on Radio Suara Kendari. This research was conducted at the Faculty of Social and Political Sciences of Haluoleo University. The informants of this study are the students of communication studies who actively listen to the broadcast of Take and Give RadioSuaraKendari. This study used snow ball sampling technique in determining the informants. In analyze the data; the researcher applied qualitative descriptive analysis.The result of this study indicated that the Communication StudentsPerception ofTake and Give Program on Radio Suara Kendari isvery good. This can be seen from the satisfaction of the informants in meeting their needs to obtain or get entertainment, or information. The good response that given also cannot be separated from the hard work of Radio SuaraKendari, especially the broadcasters of the take and give program, which managed to make the audiences or listeners, pay attention to receive and to understand what the broadcasters served to the listener. Keywords: Perception, Take and Give, Radio Suara Kendari